P180 Systematic Review Of Continuous Interscalene Brachial Plexus Block For The Shoulder Or Humerus Surgery Patients. (15th August 2013) - Choi, M; Ko, Y; Yeon, J; Oh, H; Han, S
Abstract : Objective: The safety and effectiveness of continuous interscalene brachial plexus block for the shoulder or humerus surgery. Methods: Continuous interscalene brachial plexus block for the shoulder or humerus surgery patients was assessed using 8 domestic databases including Korea Med and Ovid-MEDLINE, Ovid-EMBASE and Cochrane Library. Through a search strategy, a total of 348 works were identified and total of 21 works were included in the final assessment. Two reviewers screened all references independently, for assessing included articles quality and extracted data. Results: Side effects of the drug were reported to have occurred less or at similar level in the intervention group than the control group, although procedure related complications were reported to have occurred more often in the intervention group compared to the control group. The average pain score following the surgery was reported to be significantly lower or similar for the intervention group compared with the control group. The intervention group also had lower or similar level of quantity of additional analgesics used in comparison to the control group. In addition, the intervention group displayed either similar or higher level of satisfaction of patients on the pain control method. Conclusion: Continuous interscalene brachial plexus block was assessed to be a safe and effective technology when used for the purpose of reduction in pain in shoulder or humerus surgery patients since it was found to be relatively safe when compared with the existing procedures, and similar or more effective in terms of pain control and usage of additional analgesics in comparison to the existing pain control methods.